Conventional and UAV-Based Aerial Surveys for Long-Term Monitoring (1954–2020) of a Highly Active Rock Glacier in Austria - Kaufmann, Viktor; Kellerer-Pirklbauer, Andreas; Seier, Gernot (Frontiers in Remote Sensing, 2021)
Rock glaciers are creep phenomena of mountain permafrost. Speed-up has been observed on several rock glaciers in recent years and attributed to climate change. Although rare, related long-term studies are nevertheless essential to bring a climate perspective to creep velocity changes. In the present study, we focused on changes both in the surface creep velocity and volume of the Leibnitzkopf rock glacier (Hohe Tauern Range, Austria) in the period 1954–2020. We applied 3D change detection using aerial images of both conventional (12 epochs between 1954 and 2018) and unmanned aerial vehicle (UAV)-based aerial surveys (2 epochs, 2019 and 2020), and combined this with ground and air temperature data. Photogrammetric processing (structure-from-motion, multi-view stereo) of the multi-temporal dataset resulted in high-resolution digital orthophotos/DOPs (5–50 cm spatial resolution) and digital elevation models/DEMs (10–50 cm grid spacing). Georeferencing was supported by five externally triangulated images from 2018, bi-temporal aerial triangulation of the image data relying on stable ground around the rock glacier, measured ground control points (2019 and 2020), and measured camera locations (PPK-GNSS) of the UAV flight in 2020. 2D displacement vectors based on the multi-temporal DOPs and/or DEMs were computed. Accuracy analyses were conducted based on geodetic measurements (2010–2020) and airborne laser scanning data (2009). Our analyses show high multi-annual and inter-annual creep velocity variabilities with maxima between 12 (1974–1981) and 576 cm/year (2019–2020), always detected in the same area of the rock glacier where surface disintegration was first observed in 2018. Our volume change analyses of the entire landform for the period 1954–2018 do not indicate any significant changes. This suggests little permafrost ice melt and/or general low ice content of the rock glacier. Analyses of the temperature data reveal a close relationship between higher temperatures and rock glacier acceleration despite the high probability of low ice content. This suggests that hydrogeological changes play an important role in the rock glacier system. The paper concludes with a summary of technical improvements and recommendations useful for rock glacier monitoring and a general view on the kinematic state of the Leibnitzkopf rock glacier.